Growth and water relations of roselle grown on bris soil under partial root zone drying - Roshita Ibrahim; Khawarizmi Mohd Aziz; Adzemi Mat Arshad; Sayed Mohamed Zain Sayed Hasan (Penerbit Universiti Kebangsaan Malaysia, 2015)
Twenty-four roselle plants were grown on BRIS soil in a greenhouse to evaluate the effects of partial rootzone drying (PRD) technique on the growth, water relation and its quality. PRD is one of the deficit irrigation methods applied in order to face global water scarcity by alternating left and right roots to be irrigated within certain period of time. Four treatments were compared viz. i) Control (100% full irrigation, CI), ii) 20% PRD (80% irrigation), iii) 40% PRD (60% irrigation) and iv) 60% PRD (40% irrigation) with three replications. No significant differences were recorded for volumetric soil water content (θ) of the roselle plants under different PRD treatments throughout 84 days experimental period. Plants subjected to 60% PRD showed a significant reduction in stem water potential (Ψstem) as compared to control plants on Day 56. While all plants subjected to PRD experienced mild water stress, they suffered no serious damaging effects in terms of calyx fresh weight, calyx number or total anthocyanins as compared to control plants. In fact, plants in the 20% PRD treatment tended to have higher total anthocyanins than control plants, resulting in better postharvest quality. This study shows that it is possible to reduce 20% irrigation water without serious adverse effects on the growth, yield, and postharvest quality of roselle.